IMPLEMENTATION OF RECLAME TAX COLLECTION POLICY IN TAX AND RETRIBUTION SERVICE UNITS OF CENGKARENG REGION, JAKARTA BARAT ADMINISTRATION CITY - Ria Noviyanti; Zaman Zaini (International Peneliti Ekonomi, Sosial dan Teknologi, 2019)
Implementation of Advertisement Tax Policy in the Cengkareng Regional Tax and Retribution Service Unit in West Jakarta City Administration. This thesis aims to analyze and evaluate the implementation of policies, constraints, and efforts to collect advertisement tax in Cengkareng UPPRD, using qualitative research methods through interview techniques and documentation studies. This study uses the implementation model theory of Van Meter and Van Horn by examining 6 aspects including 1) Standards and policy objectives, 2) Characteristics of implementing organizations, 3) Resources, 4) Implementing Attitudes, 5) Communication between implementing agencies, 6 ) Social, environmental and economic conditions. Based on the results of research that has been done, it is known that 3 aspects have been going well including 1) aspects of standards and policy objectives, 2) aspects of the characteristics of implementing organizations, and 3) aspects of implementing attitudes, while aspects of resources, aspects of communication between implementing agencies and social aspects, the environment and economy still do not support the implementation of advertisement tax collection policy at UPPD Cengkareng. In this study, researchers found that aspects of technology and information are important aspects that must also exist to be able to complete 6 other aspects so that policy implementation runs well and optimally.